Physical simulation of remaining oil distribution in the 3rd-order architecture unit in beach sand reservoir - Liu, Taixun; Fawad, Nadir; Li, Chao; Li, Haitao; He, Ruiwu; Xu, Jian; Ahmad, Qazi Adnan (Frontiers in Earth Science, 2023)
Oilfield development's primary objective has changed in recent years as a result of a deeper focus on oilfield exploration and possible reservoir oil extraction. These days, the distribution and characteristics of the residual oil are a highly hot topic. This research provides a physical simulation of the leftover oil distribution in the 3rd-order architectural unit in the coastal reservoir. Based on the reservoir geometry and compositional sequence, the 3rd-order architecture unit in coastal reservoir can be divided into three types: layered, plate-like, and trough-like architecture units. Water flooding simulation experiment is performed to simulate the remaining oil (RO) distribution pattern and the controlling effect of the interlayer in these architecture units. The simulation results revealed that; in the layered architecture unit with reverse graded bedding, RO is mainly distributed between interlayers and on the smallest particle size of sands at the bottom of the architecture unit. The horizontal distribution of mudstone interlayer has profound effect in blocking the longitudinal migration of fluid. Secondly, in the plate-like architecture unit with roughly uniform particle size, RO is mainly residing in the middle portion, separated by the clay interlayers with sporadic remaining oil in the upper and lower part of the model. The oblique distribution of the clay interlayer has a significant effect on the blocking of the lateral migration of the fluid. Thirdly, in the trough-like architectural unit with normal graded bedding, the RO is mainly distributed on the location of the smallest particle size at the upper part of the model as well as on the ridge-like parts formed by the interlayer’s intersection. Trough-like clay interlayer can promote the fluid movement. RO distribution patterns from the current experiment can be used to explore the remaining oil in coastal reservoir of similar oilfields.